2021
DOI: 10.1007/s11096-021-01355-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring co-dispensed drug use in patients on sevelamer or polystyrene sulfonate to identify potential novel binding interactions: a cross sectional in silico study

Abstract: BackgroundSevelamer and polystyrene sulfonate are used for treating hyperphosphatemia and hyperkalaemia in chronic kidney disease patients. Because of their binding properties, these resins potentially bind other drugs in the gastrointestinal tract, thereby decreasing their bioavailability and clinical effectiveness. AimThe aim of this study was to explore co-dispensed drug use in patients on sevelamer or polystyrene sulfonate to identify potential novel binding interactions. MethodIn this in silico study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A previous study of our research group identified several new potential binding interactions with polystyrene sulfonate, based on their chemical structure, one of which was the tricyclic antidepressant amitriptyline. Amitriptyline is positively charged in the gastrointestinal tract and thereby susceptible to binding to the negatively charged polystyrene sulfonate [15]. Amitriptyline is usually used as an analgesic for neuropathic pain in patients with CKD and haemodialysis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of our research group identified several new potential binding interactions with polystyrene sulfonate, based on their chemical structure, one of which was the tricyclic antidepressant amitriptyline. Amitriptyline is positively charged in the gastrointestinal tract and thereby susceptible to binding to the negatively charged polystyrene sulfonate [15]. Amitriptyline is usually used as an analgesic for neuropathic pain in patients with CKD and haemodialysis [16,17].…”
Section: Introductionmentioning
confidence: 99%